Justification of Sustainable Investment by the Management Theories of Sustainable Goal Setting and Stakeholder - Zonienė, Aurelija; Valiulė, Violeta (Socialiniai tyrimai, 2019)
Shifting societal understanding of sustainability can be tied to the potential of long-term growth of a company. This is reflected in the organization’s approach to sustainable investment and its management. Mostly, sustainable investment is based on the theories of economics and there is no clear consensus regarding the justification of sustainable investment by the theories of management.The purpose of this paper is to justify the benefits of sustainable investment for organizations by the two theories of management (modern and classic): Sustainable goal setting and Stakeholder theory. Those two theories have been chosen because they are believed to better correspond with the principles of sustainable investment.The question of the research is how to justify sustainable investment by Sustainable goal setting and Stakeholder theories. The aim of the research is to justify sustainable investment by Sustainable goal setting and Stakeholder theories.It has been found out that Sustainable goal setting theory and Stakeholder theory are related, overlapping and equally important in sustainable investment.
Keywords: sustainable investment; sustainable goal setting theory; stakeholder theory